Measuring OEE in Malaysian palm oil mills - Baluch, Nazim Hussain; Abdullah, Che Sobry; Mohtar, Shahimi (Institute of Interdisciplinary Business Research, 2012)
Today maintenance is considered as a strategic and integral part of the business process and it is an established fact that “It creates additional value.” As the understanding of the strategic importance of maintenance has risen, so too has, the efforts to control, measure, and better manage this function.Performance Management and measurement is important because it identifies current performance gaps between current and desired performance and provide indication of progress towards closing the gaps.Carefully selected KPIs identify precisely where to take action to improve performance.OEE, a vital KPI of TPM, is used to evaluate performance of maintenance management; it is an index frequently used in the manufacturing industries to calculate the overall equipment effectiveness of a production system or part of it.This paper examines the importance of maintenance management performance evaluation, determines the effectiveness of OEE as a primary performance metric and explains its three main factors that make up the calculation process in the context of Malaysian palm oil mills.